A Feasibility study on Agos a pervious concrete batching plant - Almario, Krisha Angela D.; Castro, Andrea Coleen K.; Endaya, Roewe A.; Rellores, Genevee (Diliman, Quezon City College of Engineering, 2013)
Pervious concrete is a type of concrete that lets water pass through. This type of concrete has been used in Europe, Japan, Canada and USA. It is made up of cement, water, coarse aggregates and sometimes with fine aggregates. The lack of fine aggregates creates voids in the concrete making infiltration possible. The infiltration rates of pervious concrete ranges from 1.56 ft/min to 7.08 ft/min. At the same time, it helps manages storm water runoff. These make pervious concrete an ideal concrete to use for constructing roads in the Philippines that are most affected by flood. Other benefits of pervious concrete include noise reduction, lower temperature, skid resistance, and lower cost. On the downside, the lack of fine aggregates decreases the compressive strength of pervious concrete limiting its use to low bearing applications, such as barangay roads. Agos, Incorporated places itself as a supplier of ready-mixed pervious concrete. Based on the properties of pervious concrete, Agos has selected its target market to be construction firms who construct barangay roads in Region IV as Region IV has many flood prone areas. Interested clients can place their orders through the phone calls or by directly visiting the company. Pervious concrete will soon be delivered to the site using the company's transit mixer trucks. The price of pervious concrete is estimated to be P2,850/m3 which is lower than the average concrete price of P3,ooo/m3. This is possible because unlike conventional concrete, significantly fewer fine aggregates are needed. Through symposiums, expositions, community projects and other promotional materials, Agos, Inc. aims to increase the awareness of pervious concrete's environmental benefits and attract its target market and other interested users to use pervious concrete as an alternative to conventional concrete. Agos will be located in AG&P Special Economic Zone in Batangas with a land area of 2400 m2. The capacity of the batching plant is 35 m3/hr following a chase demand production strategy. The raw materials (cement and aggregates) will be procured from the Republic Cement Corporation of Lafarge Associated Companies which is also located in Batangas. The equipment to be used follows the typical equipment needed in any concrete batching plant. These are concrete mixer, cement silo, screw pump conveyer, water tank, aggregate bins, control panel and software, and transit mixers. Starting this project will cost Agos a total of P70,028,822. This is comprised of the pre-operating expenses, capital expenses and first quarter operating costs. P54 M will be borrowed from SSS under the Industry Loan Program. This will be payable in 5 years with 11% interest per annum. Meanwhile, P18 M will come from the owners/investors. A total of P72 M will therefore be raised. This amount will be used for acquiring equipment, building, land, raw materials and other investment expenditures, and to finance first quarter operating costs. Analysis of the Agos' financial standing shows that company is liquid and profitable. With an IRR of 168%, the Agos Pervious Concrete Batching Plant is worth investing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Agos, Incorporated; Participatory monitoring and evaluation (Project management); Concrete construction industry; Concrete mixers